ANALISIS EKSPERIMENTAL KINERJA TURBIN VORTEX AKIBAT PERUBAHAN TINGGI IMPELLER TIPE SUDU BERPENAMPANG LURUS - Raden Hengki Rahmanto; Muhammad Syaifuddin AZ; Geri Setiadi (Jurnal Ilmiah Teknik Mesin, 2020)
The use of fossil fuels is now increasing while these resources will be used up if used continuously and these energy resources require a long process to be reused. Alternative energy sources and renewable energy reserves in Indonesia are quite large, but their development has not been optimal because of the geographical gap between the location of energy supply and demand and high technology investment to develop new renewable energy-based technologies and the application of new renewable energy technologies, especially in the electricity sector and as fuel. Based on research that has been carried out on the mechanics of involute inward vortex inflows, the optimal size of the impeller height has not yet been found. This study uses an experimental research method, namely by making a vortex turbine with a straight-section blade type that has a blade height of 180 mm, 210 mm and 240 mm with a water capacity of 10.1471 L / s. loading variations used 3 kg, 3.5 kg, 4 kg, 4.5 kg, 5 kg, 5.5 kg and 6 kg. Tests will be carried out with the above variables on torque, mechanical power and vortex turbine efficiency. The results obtained that the height of the impeller 210 mm has torque, mechanical power and optimal efficiency than the impeller height of 180 mm and 240 mm. The highest mechanical power produced by turbines with an impeller height of 210 mm at a capacity of 10.1471 L / s with a load of 6 kg has a mechanical power of 24.28 watts. The highest efficiency is owned by turbines with a height of 210 mm occurred at a capacity of 10.1471 L / s with a loading of 6 kg, having an efficiency of 37.93%. This is because by adding the height of the impeller to the turbine, the area of ​​the blade affected by the impact of the water fluid becomes more, even when given the turbine loading conditions are not completely submerged. The more blade area submerged by fluid has a more significant influence on the power and efficiency produced than turbines that are resistant to loading even though the turbine is perfectly submerged.